Implementation of the Family Hope Program (PKH) in providing social protection to the people Cot Karieng - FNU Munadissidqi; Hasbi Ali; Yusrijal Abdar (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
This research aims to investigate the implementation, forms of protection, and inhibiting factors of the Family Hope Program (Program Keluarga Harapan or PKH) in the fields of education and health in providing social protection to the community. This study employs a qualitative approach with a descriptive research design. Data collection is conducted through direct interviews with PKH facilitators, the village head or Keuchik, and the Beneficiary Family (Keluarga Penerima Manfaat or KPM) in Gampong Cot Karieng. The research findings indicate that the implementation of PKH is fairly successful, and this assistance program has a significantly positive impact on the community. Recipients of the PKH program perceive benefits in terms of social protection and well-being. PKH also assists in fulfilling the needs of the community, especially in the areas of health and education. However, there is emerging jealousy among other community members who do not receive these benefits, despite feeling entitled to the program. Additionally, beneficiary families sometimes face difficulties in attending monthly meetings organized by PKH facilitators. Therefore, it is hoped that the community can utilize the PKH assistance funds to improve their well-being by prioritizing their essential needs.